CONTROVERSY IN HUMAN RESOURCE MANAGEMENT IN MADRASAHS: TRENDS AND SOLUTIONS FOR IMPROVING THE QUALITY OF ISLAMIC EDUCATION - Himmah, Hanim Faiqotul; Haniatin, Maimanatin; Aisyah, Siti; Ilyana, Eka Musdalifah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study focuses on the impact of Islamic education management on character and moral development in madrasahs. The primary objective of this research is to explore how the integration of Islamic values into the curriculum and teaching methods influences students' moral and ethical awareness. The research employs a quantitative approach with a descriptive study design, utilizing data collection techniques such as questionnaires, interviews, and observations. The data is analyzed using descriptive statistical analysis to identify correlations between Islamic education management and students' character development. The findings reveal that Islamic education significantly contributes to shaping students' character and morals. The integration of Islamic values in learning helps students navigate complex moral situations and fosters a positive attitude toward others. However, challenges in implementing this approach amid rigorous academic demands require special attention. The study's implications highlight the need for adequate support for educators and curriculum policy changes to enhance the effectiveness of Islamic education in character development